Physicochemical, Microbiological and Ecological Risk Assessment of Heavy Metals in Okpaka Section of Warri River, Delta State, Nigeria - C. L. Diejomaoh; L. O. Nwogor (Journal of Applied Sciences and Environmental Management)
Environmental pollution remains a critical global concern, contributing to increased rates of mortality and morbidity, while threatening both human health and ecosystems. Hence, the objective of this paper was to investigate the physicochemical, microbiological, and ecological risks assessment of heavy metals in the Warri River, Delta State, Nigeria using appropriate standard procedures. The findings indicated that pH values ranged from 5.00 to 6.50, with an average of 6.20; dissolved oxygen levels varied between 4.60 and 4.81 NTU, averaging 4.21 NTU. Chemical Oxygen Demand (COD) ranged from 9.02 to 11.90 mg/L, with an average of 9.40 mg/L. Copper concentrations varied from 0.03 to 0.62 mg/L, with an average of 0.43 mg/L, while lead (Pb) concentrations ranged from 0.05 to 0.09 mg/L, with an average of 0.07 mg/L. Cadmium (Cd) levels ranged from 0.04 to 1.05 mg/L, with an average of 0.08 mg/L. The total heterotrophic bacteria (THB) ranged from 1.69 × 10³ to 3.21 × 10³ CFU/mL, with an average of 2.51 × 10³ CFU/mL. Total coliform counts ranged from 3.8 to 9.6, with an average of 8.2. Both lead and cadmium concentrations exceeded regulatory safety thresholds. The microbiological analysis revealed high counts of total heterotrophic bacteria and coliforms, suggesting potential fecal contamination and an increased risk of waterborne diseases. Furthermore, the ecological risk assessment highlighted cadmium as the most hazardous heavy metal present in the river. These results underscore the urgent need for effective pollution control strategies and sustainable water management practices to protect both public health and environmental integrity.